ANALISIS IMPLEMENTASI METODE JAMA DALAM PEMBELAJARAN TAHFIDZ AL-QUR’AN DI KELOMPOK B PAUD BKB KEMAS MAWAR - Haeriah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to analyze the implementation of the jama' method in learning tahfiz al-Qur'an at the BKB Kemas Mawar Early Childhood Education (PAUD) institution. The congregational method is a method of memorizing the Qur'an that emphasizes memorization collectively or in groups. This research uses a qualitative approach with a case study type. Data collection was carried out through interviews, observation and documentation. The results of the research show that the implementation of the jama' method in PAUD BKB Kemas Mawar has been implemented well. This method is considered effective in increasing motivation and the ability to memorize the Koran in young children. Apart from that, the jama' method is also able to create a fun and collaborative learning atmosphere between students. However, there are several obstacles to its implementation, such as variations in children's abilities, availability of teaching resources, and limited learning time. Therefore, efforts are needed to optimize the application of the jama' method through improving teacher quality, more efficient time management, and adapting to student characteristics. Keywords: Qualitative, Tahfidz Al-Qur'an, Jama Method.